Synthesis of amidated pectin with amino acid using ultra-low temperature enzymatic method and its evaluation of fat mimic characteristics. (April 2022) - Zheng, Chenmin; Zhang, Zhigang; Ding, Nengshui; Huang, Bingqing; Zhang, Guoguang; Fei, Peng
Abstract: The grafting of amino acid [glycine (Gly), L (+)-glutamic acid (Glu) and l -lysine (Lys)] onto pectin at the ultra-low temperature solid-liquid two-phase interface under papain catalysis was investigated, and the effects of amino acids amidation on the viscosity and gel properties of pectin were analysed. Fat-mimic characteristics were also evaluated. Fourier transform infrared spectrometer, the proton NMR and X-ray photoelectron spectroscopy were used to characterise and discuss the synthesis mechanisms of Gly-amidated pectin (LMP-Gly), Glu-amidated pectin (LMP-Glu) and Lys-amidated pectin (LMP-Lys). Results suggested that papain still exhibited synthesis function under ultra-low temperature reaction. The amino group of amino acid and the carboxyl group of pectin bound at the interface between organic and water phases to form amidated pectin under papain catalysis. The grafting rates of LMP-Glu, LMP-Gly and LMP-Lys were 13.04%, 9.32% and 11.71%, respectively. Under low calcium concentration and no sugar, the dynamic viscosity and gel properties of the amidated pectin were better than those of the low-esterified pectin, and its gel particle size met the requirements for fat mimics. Graphical abstract: Image 1 Highlights: Pectin was amidated by amino acid through ultra-low temperature enzymatic method. At ultra-low temperature, the amide synthase activity of papain was dominant. The amidated pectin can form gels under low calcium and no sugar conditions.